Separation, synthesis, and cytotoxicity of a series of mogrol derivatives. Issue 7 (2nd July 2020) - Wang, Lei; Li, Lianchun; Fu, Yuxia; Li, Bingchen; Chen, Bing; Xu, Feng; Li, Dianpeng
Abstract: Four metabolites of mogrol were separated, identified and characterized. Their antitumor activity was evaluated, and the results showed side chain modification would probably enhance the cytotoxicity. Therefore, three types of amines, alcohols and rigid planar derivatives were synthesized. Compounds 20 and 21 containing a tetrahydro- β -carboline structure at the end of the side chain exhibited IC50 values around 2–9 μM against A549 and CNE1 cell comparing with 80–90 μM of mogrol. Structure analysis suggested that the perhydrocyclopentanophenanthrene moiety and the tetrahydro- β -carboline moiety could probably enhance the activity through an intramolecular synergistic effect.